Ancient DNA at the edge of the world: Continental immigration and the persistence of Neolithic male lineages in Bronze Age Orkney - Dulias, Katharina (2022)
Raw sequencing reads of ancient samples produced for this study have been deposited in the European Nucleotide Archive under accession no. PRJEB46830. Modern mitochondrial genomes generated as part of this study have been deposited in GenBank, accession nos. MZ846240 to MZ848095.